Helicobacter pylori Infection of Primary Human Monocytes Boosts Subsequent Immune Responses to LPS - Frauenlob, Tobias; Neuper, Theresa; Mehinagic, Muamera; Dang, Hieu-Hoa; Boraschi, Diana; Horejs-Hoeck, Jutta (Frontiers in Immunology, 2022)
Infection with Helicobacter pylori (H. pylori) affects almost half of the world’s population and is a major cause of stomach cancer. Although immune cells react strongly to this gastric bacterium, H. pylori is still one of the rare pathogens that can evade elimination by the host and cause chronic inflammation. In the present study, we characterized the inflammatory response of primary human monocytes to repeated H. pylori infection and their responsiveness to an ensuing bacterial stimulus. We show that, although repeated stimulations with H. pylori do not result in an enhanced response, H. pylori-primed monocytes are hyper-responsive to an Escherichia coli-lipopolysaccharide (LPS) stimulation that takes place shortly after infection. This hyper-responsiveness to bacterial stimuli is observed upon infection with viable H. pylori only, while heat-killed H. pylori fails to boost both cytokine secretion and STAT activation in response to LPS. When the secondary challenge occurs several days after the primary infection with live bacteria, H. pylori-infected monocytes lose their hyper-responsiveness. The observation that H. pylori makes primary human monocytes more susceptible to subsequent/overlapping stimuli provides an important basis to better understand how H. pylori can maintain chronic inflammation and thus contribute to gastric cancer progression.